2003
DOI: 10.1159/000073918
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Histological and Radiographic Caries Lesion Depth Measured in Images from Four Digital Radiography Systems

Abstract: The aim of this study was to compare the accuracy of approximal caries lesion depth measurements in radiographs from four digital systems. Two CCD-based sensors, Dixi (Planmeca) and Sidexis (Sirona), and two phosphor plate systems, Digora (Soredex) and DenOptix (Gendex), were used to record radiographs of 177 extracted human teeth. Sixty-four radiographically visible lesions were selected and measured by 4 observers in the digital radiographs and in digital photographs of histological sections of the teeth. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 7 publications
0
34
2
2
Order By: Relevance
“…4,5 Radiographic examination is widely used and easy to perform for the diagnosis of approximal caries. [5][6][7][8][9] In the early 1990s, digital radiographic systems were launched, yielding the great possibility of manipulating image brightness and contrast to improve diagnosis. 10 Nevertheless, the radiographic diagnosis of caries lesions depends on the contrast and, therefore, demineralization has to encompass at least 30-40% of the enamel layer to be observed, implying an irreversible mineral loss.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Radiographic examination is widely used and easy to perform for the diagnosis of approximal caries. [5][6][7][8][9] In the early 1990s, digital radiographic systems were launched, yielding the great possibility of manipulating image brightness and contrast to improve diagnosis. 10 Nevertheless, the radiographic diagnosis of caries lesions depends on the contrast and, therefore, demineralization has to encompass at least 30-40% of the enamel layer to be observed, implying an irreversible mineral loss.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that direct digital systems have a number of advantages when compared with conventional film. 2,[7][8][9][10][11][12][13] For example, the exposure dose should, in principle, be reduced since digital images are less likely to show the high frequency of exposure or processing artefacts often experienced with conventional film; working time from image exposure to image display is reduced (no wet processing is involved) and image communication is easier. Another potential advantage of digital imaging is the ability to perform image quality enhancements such as contrast and density modulation, which may increase diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Still, the digital method has other advantages such as: the elimination of the chemical developing process, the immediate availability of the image, the image enhancement function (mostly changes of density and contrast), the small storage space needed, the use in teleradiology, the availability in multiple reprints, and the lower contamination of the environment [11,13,21,28].…”
Section: Discussionmentioning
confidence: 99%